Alice: Easy to Use Interactive 3D Graphics - , Jefiey S. Pierce; Audia, Steve; Burnette, Tommy; Christiansen, Kevin; Cosgrove, Dennis; Conway, Matt; Hinckley, Ken; Monkaitis, Kristen; Patten, James; Shochet, Joe; Staack, David; Stearns, Brian; et al. (UIST '97 Proceedings of the 10th annual ACM symposium on User interface software and technology, 1997)
Alice is a rapid prototyping system used to create three dimensional graphics simulations like those seen in virtual reality applications. Alice uses an interpreted language called Python as its scripting language to implement user actions. This interactive development environment allows users to explore many more design options than is possible in a compiled language environment. The alpha version of Alice for Windows 95 is available for free over the intemet, with the beta release scheduled for August.